Integration of 21st Century Skills in Pesantren Education: An Innovative Model for Improving the Global Competence of Santri - Sodikin; Vialinda Siswati; A. Qomarudin; Akhmad Sirojuddin; Achmad Yani (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
In the context of rapid global change, pesantren face increasing pressure to equip santri with 21st-century skills essential for global competitiveness.This study explores how Al-Yasini Islamic Boarding School integrates 21st-century skills within an Islamic framework to sustain its religious identity while enhancing global competitiveness. Using a qualitative descriptive approach with a case study design, data were collected through in-depth interviews with kiai, teachers, and students, along with classroom observations and document analysis. Thematic analysis was applied to identify key patterns in leadership, independence, and digital literacy, while methodological triangulation was employed to ensure analytical credibility. The findings reveal that the integration of Islamic soft skills, the 4C learning framework (critical thinking, creativity, collaboration, and communication), the digitalization of Islamic literacy, and the cultivation of leadership and independence enables the institution to produce globally competitive graduates. However, several challenges persist, including limited technological infrastructure, resistance to modernization among some Islamic boarding schools, and insufficient teacher adaptability to innovative pedagogical methods. To address these gaps, this study recommends strengthening collaboration between Islamic boarding schools, higher education institutions, and industry partners to enhance student preparedness for global challenges. The study contributes to both theory and practice by providing a context-specific yet globally relevant framework for Islamic education reform.